Death Is Not Different: The Transfer of Juvenile Offenders to Adult Criminal Courts - Mallett, Christopher A (2007)
The US Supreme Court first reviewed a state's statutory procedure for juvenile transfer to adult criminal courts in Kent v. US 1 Morris Kent was a fourteen-year-old first convicted for purse snatching and house-breaking, placed on probation, and later charged at the age of sixteen with robbery and rape. 2 Kent was arrested, presumably admitted to involvement in these crimes after seven hours of interrogation, and placed in a receiving home for one week